Способ получения трифторида азота - Акишин В. С. Валерий Сергеевич; Андриец С. П. Сергей Петрович; Гаврилов П. М. Петр Михайлович; Евстафьев А. А. Алексей Алексеевич; Короткевич В. М. Владимир Михайлович; Лазарчук В. В. Валерий Владимирович; Ледовских А. К. Александр Константинович; Салтан Н. П. Николай Павлович; Скотнов В. С. Валерий Сергеевич
опубл. 20.02.08